Landuse and Community-based Assessment of 2014 Flood Damages in Tehsil Phalia, Punjab: Landuse and Community-based Assessment of 2014 Flood Damages in Tehsil Phalia, Punjab - Hussain, Sikandar; Liaqut , Anum; Younes, Isma; Shafiq , Muhammad (International Journal of Economic and Environmental Geology, 2024)
In this study the response and feedback from the flood-hit community of Phalia (Mandi Bahauddin) obtained through local interviews and filling of questionnaires have been analyzed. Secondary data were obtained from Pakistan meteorological and local revenue departments were also statistically analyzed. Several types of damages including houses, crops, diseases, economic loss, and livestock have been considered. Pre- and Post-flood changes in the landuse, by high resolution satellite data (Landsat 8 OLI) delineated coverage of inundation of 186.85 km2 area. It has been demonstrated that Phalia tehsil was severely damaged in 2014 rainfall induced flood in Chenab river which left lasting impacts on the socio-economic lives of local communities. The major damages experienced by the people of the study area included; house damages, crop damages, diseases, economic losses and livestock damages. It is necessary that government revises the flood prevention policies based on the community response to mitigate the disaster.